Desenvolvimento de uma matriz de nanopartículas magnéticas de óxido de ferro funcionalizadas com frutalina, lectina α-D-galactose ligante de Artocarpus incisa L. - Rodrigues, Fernanda Nascimento (2022)
Iron oxide nanoparticles have good properties, which allows their use in industrial, environmental, biotechnological processes, among others, with a wide variety of applications. Frutalin is an α-D-galactose binding lectin, with several biological activities already described. Thus, the objective of this work was to develop a matrix of magnetic nanoparticles functionalized with frutalin with potential biotechnological application. The nanoparticles were obtained by coprecipitation and subjected to a surface modification process with frutalin through crosslinking with glutaraldehyde and APTES. The material was characterized by scanning electron microscopy (SEM), dynamic light scattering (DLS), zeta potential, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (DRX), thermogravimetric analysis (TGA), in addition to carrying out biological tests. The results of SEM and DLS showed that the iron oxide nanoparticles (NPFe) had an average diameter of 700 nm, while the nanoparticles functionalized with frutalin (NPFTL) showed an average diameter of 780 nm, in addition to having a rounded and uniform appearance. The FTIR showed absorption bands at 1635 and 1539 cm-1, referring to amides I and II, characteristic of proteins, which indicates the immobilization of frutalin on the surface of NPFe. XRD showed that the functionalization process did not modify the characteristic crystalline state of iron oxide. The TGA demonstrated that NPFTL presents a slower thermal degradation, compared to the free protein. The hemagglutinating assay showed that the functionalization process did not affect the three-dimensional structure of frutalin, as the protein maintained its ability to agglutinate cells. In addition, it was possible to observe the interaction of the lectin with the nanoparticles and the blood when an external magnetic field was applied and a deposition of the complex formed at the bottom of the wells was observed. The ability to recognize galactose was proven by shifting the FTIR peak at 3500 cm-1 after interaction between NPFTL and galactomannan. The matrix showed no toxicity in in vitro tests up to 2 mg.mL-1 using L929 cells. In summary, the production of the matrix of nanoparticles functionalized with frutalin proved to be efficient and with potential for future applications in purification processes involving glycoconjugates